The 21 st Century Educated Mount Kenya University Graduate and its Implications for the Practice of Higher Education - Amukowa, Wycliffe (International Journal of Social Science & Education, 2013)
The objective of this paper is to serve as the seed around which further thought on the role of the university education grows. By seeking an understanding of the 21st Century Educated Mount Kenya University graduate, the paper elucidates the role of the universities and their appropriate pedagogical approaches. In this regard, the essence of this paper is an endeavour into university’s best practices and the place of its products (graduates) into the society.
Keywords: University Education; Mount Kenya University; Temptation; Authentic